2018
DOI: 10.1111/petr.13300
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of BMI, waist circumference, and waist‐to‐height ratio for identification of subclinical cardiovascular risk in pediatric kidney transplant recipients

Abstract: Background: Kidney transplant recipients are at high risk for CV morbidity. However, the measure of obesity that best predicts CV risk has not been established.Objective: A prospective, controlled study was conducted to compare the ability of BMI, WC, and WHr to identify CV risk in pediatric kidney transplant recipients. Methods: Transplant recipients, aged 3-20 years, had echocardiogram, CIMT, BMI, WC, WHr, blood pressure, lipids, and leptin measured. Receiver operating characteristic analysis was used to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…However, additional screening measurements may aid in targeting specific potential deficiencies and facilitate a more comprehensive assessment. There is evidence in the pediatric literature that grip strength [48] and waist-to-height ratio [49,50] are measures to consider. However, additional experience with these measures in clinical practice settings is necessary before their routine use can be recommended.…”
Section: Nutrition-focused Physical Examinationmentioning
confidence: 99%
“…However, additional screening measurements may aid in targeting specific potential deficiencies and facilitate a more comprehensive assessment. There is evidence in the pediatric literature that grip strength [48] and waist-to-height ratio [49,50] are measures to consider. However, additional experience with these measures in clinical practice settings is necessary before their routine use can be recommended.…”
Section: Nutrition-focused Physical Examinationmentioning
confidence: 99%
“…In the study, normal BMI but higher WHR posed the highest risk of CAC, which suggests that patients who had normal BMI with less muscle mass or less subcutaneous fat but had high WHR with more visceral fat showed the highest risk for CAC. A recent study on transplant patients also found that WHR is a more sensitive predictor of clinical CVD risk than BMI 21 . However, the study was conducted in a relatively small number of pediatric transplant patients with a low CVD risk, and hyperlipidemia and even hypertension were included as CVD outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…18 Waist-to-height ratio has also been shown to have an optimal discriminatory capacity to predict metabolic syndrome and insulin resistance in women with kidney transplant. 19 Furthermore, Sgambat et al 20 demonstrated that WHr was superior to BMI and WC as an indicator of subclinical cardiovascular risk in pediatric RTR, and the authors suggested that WHr could be a really useful measurement for adults undergoing renal transplantation. 20 All these indications prompted us to evaluate whether WHr could also be related to other complications in renal transplantation.…”
Section: Discussionmentioning
confidence: 99%